Ada Zevin – 100 years from birth (Confluenţe Bibliologice, 2018)
In the article is described the anniversary exhibition dedicated to the plastic artist and art critic Ada Zevin and exposed in the reading room „Psycho-pedagogical, natural, real. Arts „of the USARB Scientific Library.
Keywords: Zevin Ada (1918–2005); anniversary exhibition; collection of the USARB Scientiﬁc Library; Bessarabian painters